2018
DOI: 10.1021/acs.jpca.8b00773
|View full text |Cite
|
Sign up to set email alerts
|

How Methylation Modifies the Photophysics of the Native All-trans-Retinal Protonated Schiff Base: A CASPT2/MD Study in Gas Phase and in Methanol

Abstract: A comparison between the free-energy surfaces of the all- trans-retinal protonated Schiff base (RPSB) and its 10-methylated derivative in gas phase and methanol solution is performed at CASSCF//CASSCF and CASPT2//CASSCF levels. Solvent effects were included using the average solvent electrostatic potential from molecular dynamics method. This is a QM/MM (quantum mechanics/molecular mechanics) method that makes use of the mean field approximation. It is found that the methyl group bonded to C10 produces noticea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Additionally, the anomalous intensity of the + 30 1 m 2 band when exciting via m 1 and, more generally, the activity of + 30 1 m x bands in the spectra for mFT and mClT, confirm that certain out-of-plane vibrational motions are intricately linked to torsional motion. Overall, we conclude that it is unlikely that one can express the vibtor levels of + 30 1 and + 30 2 as simply products of torsional and vibrational wavefunctions.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Additionally, the anomalous intensity of the + 30 1 m 2 band when exciting via m 1 and, more generally, the activity of + 30 1 m x bands in the spectra for mFT and mClT, confirm that certain out-of-plane vibrational motions are intricately linked to torsional motion. Overall, we conclude that it is unlikely that one can express the vibtor levels of + 30 1 and + 30 2 as simply products of torsional and vibrational wavefunctions.…”
Section: Discussionmentioning
confidence: 80%
“…Energy flow in molecules is now generally accepted as being facilitated by the coupling of both methyl torsion and vibrational motions and so is important for understanding the photophysics of molecules. 1,2 A very recent example highlights the role vibrational excitation has in light harvesting. 3 Understanding the processes occurring in complicated molecules is greatly aided by detailed studies on small molecules, and recent examples from our, the Reid and Lawrance groups have looked at toluene, 4,5,6 para-fluorotoluene (pFT) 7,8,9,10,11,12,13,14,15 and para-xylene (pXyl), 10,16,17 using a combination of fluorescence and photoionization spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, QM/MM simulations of a model all-trans retinal (rPSBAT) demonstrated how methyl substitution increased the ES lifetime, both in gas phase and non-polar solvents. 51 However, Kukura and co-workers experimentally found that photoisomerization of 10-methyl-rPSBAT (methylation at C10 in rPSBAT) in methanol is much faster than rPSBAT, 134 which has been verified using QM/MM simulations in both methanol 135,136 and in a protein environment 99 and was rationalized by a reduction in S 2 /S 1 mixing resulting in steeper ES slopes (similar to the discussion related to Fig. 10), illustrating again that the methyl group is not a pure inertial substituent.…”
Section: Typementioning
confidence: 95%
“…Furthermore, a recent study on the photexcited dynamics of methylated butadienes highlighted the importance of electronic effects of the weakly electron-donating methyl group, influencing nonradiative decay time scales and branching ratios . Electronic effects of the methylation have also been found to accelerate the photoisomerization of a methylated derivative of all-trans retinal (methylated at the C10 position) in solution. In light of such developments, we aim to resolve the mechanistic details of S 2 ( ππ *) internal conversion in AC and the role of inertial and electronic effects in its methylated derivatives using nonadiabatic dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%